2022
DOI: 10.47992/ijcsbe.2581.6942.0178
|View full text |Cite
|
Sign up to set email alerts
|

Management Students’ Perception of Industrial Internship Programme at Srinivas University, Mangaluru, Karnataka

Abstract: Purpose: The central idea of the study is to identify and examine the affecting factors towards management students’ perception of Industrial Internship programme at Srinivas University, Mangaluru, India for the academic year 2021-22. Design: Secondary data is collected by referring journal papers and books. The study includes ABCD factor analysis framework. Primary data was collected from selected 219 management students’ groups. The data was run through Jamovi software for descriptive analysis and SMART PLS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 31 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…The tables below show the determinant issues identified in scholarly publications using the ABCD framework. [82] Various studies on ABCD analysis have surveyed identifying their determinant issues which further enables identification of numerous factors affecting the particular issue. The above articles have adopted ABCD analysis considering determinant issues, moreover apart from these, there are many studies which discussed ABCD analysis with the determinant issues such as Systems & Technology [83], Multifactor Authentication Model [84], Fingerprint Biometric Attendance [85], institutional ranking system [86] and Choice Based Credit System [87], etc.…”
Section: Abcd Analysis On Affecting Factors and Critical Constituent ...mentioning
confidence: 99%
“…The tables below show the determinant issues identified in scholarly publications using the ABCD framework. [82] Various studies on ABCD analysis have surveyed identifying their determinant issues which further enables identification of numerous factors affecting the particular issue. The above articles have adopted ABCD analysis considering determinant issues, moreover apart from these, there are many studies which discussed ABCD analysis with the determinant issues such as Systems & Technology [83], Multifactor Authentication Model [84], Fingerprint Biometric Attendance [85], institutional ranking system [86] and Choice Based Credit System [87], etc.…”
Section: Abcd Analysis On Affecting Factors and Critical Constituent ...mentioning
confidence: 99%
“…(1) Identifying the researchers among the faculty members, Our research group has identified and published many such innovations and best practices already available and futuristic [47][48][49][50][51][52][53][54][55][56][57][58][59]. ARC is one of such innovation converted into best practice.…”
Section: Arc Planning Involvesmentioning
confidence: 99%